Perception of Students on Agriculture as an Occupation- A Reference to Pondicherry University Postgraduate Students - K, Amaran; Krishnamoorthy, Anbu (International Journal of Social Sciences and Management, 2023)
This research article investigates the perception of postgraduate students at Pondicherry University regarding agriculture as an occupation. The study examines the demographic characteristics of the participants and explores their perceptions of agriculture. The sample comprises 56.4% female and 43.6% male respondents aged 21 to 28. Most (93.6%) of the participants fall within the 21 to 25 age group. Regarding the family type, most respondents (75.6%) belong to nuclear families, while a minority (20.5%) reside in joint families. Regarding residence, 53.8% of the respondents live in urban areas, while slightly over one-third (46.2%) reside in rural areas. The academic backgrounds of the participants are diverse, with approximately one-third belonging to the social science stream (34.6%), management stream (33.3%), and life science stream (32.1%), respectively. The study reveals that 65.4% of the respondents have a medium level of perception towards agriculture, while 34.6% have a high level of perception towards agriculture as an occupation. The article further presents the results of statistical analyses, including an independent sample t-test and analysis of variance (ANOVA). These indicate no significant differences in perception of agriculture as an occupation across gender, nativity, course of study, and family type. These findings contribute to understanding postgraduate students’ perception of agriculture as a career option and provide insights for policymakers and educators in promoting agriculture as a viable and attractive occupation for future generations. Int. J. Soc. Sc. Manage. Vol. 10, Issue-3: 55-59.